PENGARUH KEPUASAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP PRODDUKTIVITAS KARYAWAN INSTALASI LABORATORIUM RUMAH SAKIT PEMERINTAH DI KOTA BUKITTINGGI - Inong Leli; Yuni Wardi (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
The objectives of this research were to find the The Effects of Job Satisfaction, Work Motivation and Work Disciplin toward the Employee’s Productivity  of the Laboratory Instalation  government Hospital in Bukittinggi Town. Directly or indirectly. The population of this research were Laboratory Employee’s government Hospital in Bukittinggi Town amounting to 56 ( Fivety six ) people. The sample in this research amounted to 49 ( Fourty Nine ) people. The sampling method was done by using stratified proportionate random sampling. Data collection is done by filling questionaires . Analysis of the data used is path analysis. Data processing is performed with SPSS version 17.0.for Windows. The results showed that there is significant influence between Job Satisfaction to Work Motivation (1), Job Satisfaction to Work Disciplin (2), Job Satisfaction to Employee’s Productivity (3), Work Motivation to Work Disciplin (4). Work Motivation to Employee’s Productivity (5) and Work Disciplin to Employee’s Productivity (6). Totally, the magnitude of the effect is known 52,17% directly and indirectly,while the remaining 47,83% is influenced by other factors not examined in of this research. Key words: Employee’s Productivity, Work Disciplin, Work Motivation and Job Satisfaction.